ApbZIP2-mediated enhancement of lipid productivity supports sustainable plant-based omega-3 biomanufacturing - Rong Zhou; Kairui Mu; Ya’nan Shi; Yuqin Li; Liwen Luo; Yunkai Tan; Zhenyao Wang; Yufang Tang; Xuan Li (Bioresource Technology, 2027)

DA-MOT: a directed-angle-aware multi-object tracking framework for dairy cows - Tonghui Wu; Rong Wang; Haiyan Song; Zhiyong Zhang; Qifeng Li; Zhaoyang Wang; Yan Shi; Ronghua Gao (Computers and Electronics in Agriculture, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Spiro-donor modified blue thermally activated delayed fluorescence emitters with high efficiency, narrowband emission, and excellent lysosomal targeting ability - Deli Li; Qingchao Liu; Ruizhe Xu; Wei Liu; Rong Hu; Wei Li; Shi-Jian Su; Ziyi Ge; Yuhua Tong (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

A stable shear-thinning XG-WAS@n-FeS slurry for simultaneous removal of Cr(VI) and TBBPA from water - Kaipian Shi; Junfeng An; Yu Yin; Li Yin; Ziyu Rong; Jinyu Han; Shiyin Li (Journal of Water Process Engineering, 2026)

A sustained-release gallic acid microcapsule suspension for simultaneous inhibition of Microcystis aeruginosa and control of microcystin release - Yu Yin; Kaipian Shi; Ziyu Rong; Conghui Wang; Jinyu Han; Shiyin Li; Li Yin (Journal of Environmental Chemical Engineering, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Dynamic modeling and numerical simulation of dense particle multiphase flows in resonant acoustic mixing - Jingming Zhang; Mingming Shi; Bao Rong; Gouping Wang; Da Li; Xiaoting Rui (Chemical Engineering Journal, 2026)

Synergistic organic–inorganic hybrid interlayer enables tunable Zn2+ desolvation and nucleation toward dendrite-free zinc metal anodes - Xiangzhong Kong; Zicong Wang; Weijia Lv; Yuyang Ding; Xi Chen; Zhongmin Wan; Shi Li; Liya Rong (Chemical Engineering Journal, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Pesticide exposure in Eriocheir sinensis: Oxidative stress, endocrine disruption, gut–hepatopancreas axis impairment, and systems toxicology - Shi-Rong Li; Dan-Dan Bian; Xiang Lu; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

Exogenous dust-induced snow albedo reduction and radiative forcing over the Third Pole - Liang Li; Keqin Duan; Ting Yang; Yuhan Qi; Rong Chen; Peihong Shi (Journal of Hydrology, 2026)

Denitrification-enhanced anaerobic digestion for stable synergy of hydrolysis and methanogenesis of N, N-dimethylformamide by nitrate addition: Delayed stimulation effect for successful enrichment of functional microorganisms - Junjie Zhou; Zhihao Shi; Tao Zhang; Yao Xu; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; Zhe Kong (Environmental Research, 2026)

An inflammation-targeted hydrogel for the synergistic treatment of colorectal cancer and associated neuropsychiatric dysfunction - Keying Chen; Na Li; Anni Ren; Lingling Yang; Pei Xie; Yong Gao; Yanwu Li; Ying Tang; Rong Zhang; Huafeng Pan; Bangjiang Fang; Tongkai Chen; et al. (Chemical Engineering Journal, 2026)

Solar-driven green degradation of lignin toward sustainable aromatics via BiVO4/Zn4In2S7 S-scheme heterojunction - Qunshuai Li; Luxin Zhang; Weiwei Shi; Sishang Ge; Menglu Hu; Rong Chen (Chemical Engineering Journal, 2026)

Sequential input of dissolved organic matter and phosphate alters their competitive adsorption at ferrihydrite-water interfaces - Zezhen Ren; Shiwen Hu; Yuzhen Liang; Zhenqing Shi; Rong Li (Chemical Geology, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Multipathway Pesticide Exposure and Cross‐Scale Risk Assessment in Integrated Rice–Crab Aquaculture - Dan‐Dan Bian; Shi‐Rong Li; Bo‐Ping Tang; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
Integrated rice–crab co‐culture represents a sustainable agroecosystem, yet a critical conflict arises: pesticide applications necessary for rice cultivation undermine the health of the co‐cultured Chinese mitten crab ( Eriocheir sinensis ) and jeopardize system sustainability. To address this challenge, a comprehensive analytical framework is developed, linking multipathway pesticide exposure, molecular toxicity mechanisms, cross‐scale risk assessment, and resilience‐oriented governance. This framework systematically reviews the environmental fate and exposure dynamics of pesticides in paddy fields, as well as their toxicokinetics and tissue‐specific bioaccumulation in E. sinensis . Moving beyond descriptive toxicology, the study integrates “effect hierarchy” and “mechanistic network” perspectives to unravel cascading toxicity pathways, spanning oxidative stress, neuroendocrine disruption, cellular pyroptosis, and immune suppression. The limitations of conventional risk assessment in such a complex system are critically examined, with emphasis on the dual risks to crab population resilience and human food safety. To mitigate these challenges, a novel, mechanism‐informed “Prevent–Intercept–Protect–Adapt (PIPA)” framework is proposed to bolster system resilience, combining green pest control, eco‐engineering, host health enhancement, and smart monitoring. This review enhances theoretical understanding of contaminant impacts in multitrophic systems and offers actionable management strategies to promote the sustainable development of integrated aquaculture.

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Mitigating bioaerosol exposure risks in high-traffic clinics: Experimental and numerical optimization of air purifier interventions - Yongxin Wang; Zhijian Liu; Lei Jiang; Zirun Shi; Zijian Li; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Illumination-induced restructuring of extracellular polymeric substances from Klebsiella Sp. HDJY-1 drives indirect photodegradation of thifensulfuron-methyl - Jiaying Gu; Yaqi Jiao; Chunnan Zhou; Junxin Jia; Siming Li; Kai Wang; Hui Li; Hongtao Shi; Qin Zhou; Rong Liu; Li Li (Water Research, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Mineralogical tracers for magmatic and hydrothermal controls on Nb-Ta-Li mineralization: a case study from the Hailuoling granite system, Southern China - Qifei Shi; Bin Wu; Xin Gui; Qian Ren; Guanglai Li; Rong Yin; Qingfei Wang (Mineralium Deposita, 2026)

Archaeal and Bacterial Communities and Their Relations with Hydrochemistry in Gongzhu Co, a Carbon-Poor, Nutrient-Rich Basin Lake of the Qinghai–Xizang Plateau - Minhaoxue Zou; Yujie Tao; Bohan Shi; Rong Xu; Rong Wang; Yongzhen Li; Rui Han; Derui Zhu (Current Microbiology, 2026)

Nanoscale insights into the immobilization of coexisting As(V) and Cd(II) during Fe(II)-driven ferrihydrite transformation - Wei Li; Zhuohao Wu; Yang Lu; Rong Li; Qianying Sun; Zheng Liang; Wencheng Wu; Zhenqing Shi (Chemical Geology, 2026)

Multidisciplinary modeling and dynamic Kriging assisted optimization for suborbital reusable launch vehicle - Teng Long; Haoda Li; Renhe Shi; Rong Chen; Baoshou Zhang; Nianhui Ye (Advances in Space Research, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

The influence of rewetting intensity on soil priming after drought - Yijin Lv; Rui Zhang; Rong Li; Zhenqing Shi (Applied Soil Ecology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Single and combined impacts of antibiotics on aerobic denitrification: Cell growth characteristics and functional genes expressions - Rong-Rong Chang; Chang-Ze Shi; Yun-Jie Ruan; Bao-Cheng Huang; Ren-Cun Jin; Ming Dong; Wen-Bing Li (Journal of Environmental Sciences, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Research progress on the chemical composition changes of traditional Chinese medicine before and after processing based on modern analytical techniques - Xuelin Zong; Yun Shi; Ying Zhao; Yuman Li; Rong Guo; Gengyi Shang; Chenfeng Zhang; Jinyang Shen; Xun Gao; Weidong Li; Kunming Qin (Phytochemistry Reviews, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Predicting the kinetics of Cu release and transport in contaminated soils in the field - Liang Dong; Rong Li; Wenxia Wang; Zhifang Xiao; Zezhen Ren; Qianting Ye; Zhenqing Shi (Applied Geochemistry, 2026)

Effects of state of charge on characteristics of particle emissions from lithium nickel cobalt aluminum oxide/ silicon-carbon cylindrical batteries during thermal runaway - Weifeng Li; Jie Liu; Yao Xue; Zhenhai Gao; Deping Wang; Shuli Chen; Xinqi Liu; Changru Rong; Jiawei Shi (Process Safety and Environmental Protection, 2026)

Direct CH4 electrosynthesis from CO2 via unmodified commercial carbon black: Structural synergy and defect-driven catalysis - Rong-Chun Zhong; Yu-Nan Liu; Zengrong Wang; Li-Yuan Zhao; Teng Shi; Qiang Sun (Fuel, 2026)

Remediation of ternary heavy metal-polyethylene microplastics co-contaminated soil using co-modified biochar with deep eutectic solvent and warm patch: competitive interactions, mechanistic insights, and microbial community response - Luxin Zhang; Xiaobing Liu; Sishang Ge; Weiwei Shi; Rui Zhang; Chaoyang Li; Rong Chen (Environmental Research, 2026)

Synergistic (002) texturing and interfacial CuZn5 alloying on 3D ridge-like Cu substrates for dendrite-free Zn anodes - Xiangzhong Kong; Zicong Wang; Yong Liu; Zhilong Yao; Xi Chen; Zhongmin Wan; Shi Li; Liya Rong (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Ferroptosis at the intersection of radiotherapy and immunotherapy - Gui-Xia Wei; Ya-Qin Zhao; Rong Tang; Hua-Shan Shi; Zhi-Ping Li (Cancer and Metastasis Reviews, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Research on the fungi in dry-cured hams from different regions and exploration of new resources of flavor yeast - Wucong Zhou; Ai Zelin; Zilin Chen; Zhengyang Bao; Minxuan Shi; Chenghan Rong; Shuqing Yan; Xinzhu Zhang; Chunbao Li; Kai Shan (Food Research International, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Novel compound bacterial agent effects on pig farm wastewater denitrification and nitrogen transformation - Rong Gao; Zhuangzhuang Liu; Weikun Li; Liu Lou; Tong Xu; Lin Shi; Jie Cao; Jun Fang; Gang Liu (Bioresource Technology, 2025)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

Unexpected carbon emissions: impact evaluation of China’s electricity market reform - Beibei Shi; Xiaolan Li; Pengge Li; Nan Li; Rong Kang (Environment, Development and Sustainability, 2025)

Estimating the overlooked contribution of adsorption effects on CH4 release in wetland soils using a reactive transport model - Cheng Bei; Peng Liao; Kai Yu; Zhenqing Shi; Rong Li (Journal of Hydrology, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Coffee intercropping reduces soil N2O and N2 emissions: Empirical test and meta-analysis - Ronghua Li; Nanke Ma; Yue Shi; Hao Sun; Ziman Yang; Yun Zhou; Liyin Li; Syed Turab Raza; Tao Ye; Li Rong; Leqi Fang; Zhe Chen; et al. (Journal of Environmental Management, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Multi-scale piezoresistive foam composed of graphene skeleton and vertical WS2 nanosheets designed for wearable detection/protection applications - Tengyue Song; Minxuan Xu; Yueqin Shi; Xin Li; Hang Wang; Zhe Kong; Suyu Sheng; Qi Zhang; Rong Xiang (Chemical Engineering Journal, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Exploring the dual role of anti-nutritional factors in soybeans: a comprehensive analysis of health risks and benefits - Dakai Di; Shudong He; Rong Zhang; Kuan Gao; Min Qiu; Xingjiang Li; Hanju Sun; Sophia Xue; John Shi (Critical Reviews in Food Science and Nutrition, 2025)

Preparation of high-performance ceramic conductive membranes and applications as the anode and cathode in electrochemical MBRs: antifouling performance and mechanisms - Jinzhuo Shi; Yisong Hu; Songhua Li; Wenqian Xiao; Rong Chen (Journal of Water Process Engineering, 2025)

Spatial distribution, speciation, and release behavior of exogenous copper in soil aggregates: The role of aggregate structural reorganization - Zhifang Xiao; Rong Li; Yijin Lv; Bin Liang; Zhenqing Shi (Journal of Hazardous Materials, 2025)

Moisture fluctuations: An important but overlooked factor in the carbon cycle - Yijin Lv; Jialiang Kuang; Rong Li; Zhenqing Shi (Journal of Environmental Management, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Phytochemical characterization and therapeutic mechanism of Xialiqi capsule on benign prostatic hyperplasia - Tengfei Chen; Dongfang Lv; Baohai Rong; Zhuozhuo Shi; Xiaolin Li; Zhichao Jia; Zhaowang Gao; Chongfu Zhong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Atrazine exposure induces TDP-43 protein translocation: A potential mechanism for prefrontal cortical neurodegeneration induced by environmental pollutants - Yuan Ma; Kaidong Wang; Yuxuan Jiao; Yujing Li; Rong Hu; Yang Li; Ge Shi; Min Huang (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electro-conductive nylon mesh assisted electro-chemical membrane bioreactor process (EMBR) for municipal wastewater treatment - Songhua Li; Yisong Hu; Jinzhuo Shi; Wenqian Xiao; Yuan Yang; Rong Chen (Journal of Water Process Engineering, 2025)

Investigation into the bromination of polybrominated dibenzo-p-dioxins and dibenzofurans - Dan Li; Rong Cao; Haijun Zhang; Yun Fan; Mingyong Zhou; Haitao Shi; Jiping Chen (Journal of Hazardous Materials, 2025)

Metal exposure is associated with cognitive function and plasma sTrem2 levels in coal miners: a cross-sectional study - Yang Li; Kaidong Wang; Ge Shi; Ai Qi; Yujing Li; Yuxuan Jiao; Rong Hu; Guilin Hu; Yonghang Li; Zhuoheng Shen; Min Huang (Environmental Research, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

In silico prediction of drug-induced cardiotoxicity with ensemble machine learning and structural pattern recognition - Siwen Li; Haojie Xu; Fengxi Liu; Rong Ni; Yinping Shi; Xiao Li (Molecular Diversity, 2025)

MilTilV: a vertically resolved microbial explicit soil organic carbon turnover model integrated the effect of tillage operation - Kaihao YE; Liang DONG; Yijin LV; Wenxia WANG; Zhifang XIAO; Junran LI; Zhenqing SHI; Rong LI (Pedosphere, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

The food application of a novel Staphylococcus aureus bacteriophage vB_SA_STAP152 and its endolysin LysP152 with high enzymatic activity under cold temperature - Yuanyu Li; Jingsha Dai; Shi Wu; Dongli Rong; Jiahui Huang; Miao Zhao; Jumei Zhang; Qinghua Ye; Qihui Gu; Youxiong Zhang; Xianhu Wei; Qingping Wu (Food Microbiology, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Green recycling of end-of-life photovoltaic modules via deep-eutectic solvents – Part B - Yuelong Yu; Jianghao Shi; Xinjie Bai; Zhansheng Zhang; Fengshuo Xi; Shaoyuan Li; Jijun Lu; Wenhui Ma; Rong Deng (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Co-doping graphitic carbon nitride with Fe atoms and oxygen-containing functional groups for the efficient photo-Fenton degradation of sulfamethoxazole - Ruiyan Zhang; Cong Yan; Qinghua Yan; Congzhe Ren; Wen Zhang; Xiaozhe Song; Xuyang Li; Lei Chen; Fangyuan Zhou; Rong Xue; Feng Shi; Chongqing Xu (Journal of Water Process Engineering, 2025)

Operational characteristics and phosphorus recycling potential of a hydroxyapatite (HAP)-anammox process at high nitrogen loading rate - Wenqian Xiao; Yisong Hu; Songhua Li; Jinzhuo Shi; Wenrui Tian; Yi Xue; Rong Chen (Journal of Environmental Chemical Engineering, 2025)

Source and variability of formaldehyde in the Fenwei Plain: An integrated multi-source satellite and emission inventory study - Liang Li; Keqin Duan; Yuyao Wu; Junhua Yang; Ting Yang; Peihong Shi; Rong Chen (Journal of Environmental Sciences, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Effects of microclimatic conditions and urban building configurations on aerodynamic characteristics and health risks of bioaerosols: Insights from idealized urban models - Zhijian Dong; Zhijian Liu; Chenxing Hu; Chenglin Ye; Yongjun Jin; Haiyang Liu; Rui Rong; Yuchen He; Li Chen; Chuanchen Li; Yaolong Shi; Yufeng Su (Sustainable Cities and Society, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Effect of magnetic field-assisted thawing on the quality and microstructure of Portunus trituberculatus meat - Rong Shi; Zhongqi Sun; Xuemei Yu; Huamao Wei; Gaoshang Li; Wenge Yang (Food Research International, 2025)

Integrating larval zebrafish model and network pharmacology for screening and identification of edible herbs with therapeutic potential for MAFLD: A promising drug Smilax glabra Roxb. - Yinjuan Xiong; Xixuan Huang; Yuxin Li; Yukang Nie; Haodong Yu; Yaqi Shi; Jiajie Xue; Zhehui Ji; Keming Rong; Xuezhen Zhang (Food Chemistry, 2025)

Wind tunnel experiments on bioaerosol dispersion and exposure risk assessment in wastewater treatment plants under natural ventilation - Zhijian Liu; Chuanchen Li; Chenxing Hu; Rui Rong; Yaolong Shi; Zhijian Dong; Chenglin Ye; Chuang Zhang (Building and Environment, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Modeling the equilibrium and kinetics of heavy metals reactions with dissolved organic matter - Qianting Ye; Pei Wang; Yuzhen Liang; Rong Li; Zhenqing Shi (Applied Geochemistry, 2025)

Linker Histone H1.4 Inhibits the Growth, Migration and EMT Process of Non-Small Cell Lung Cancer by Regulating ERK1/2 Expression - Qian Chen; Mengqi Yang; Xinyue Duan; Jie Zhang; Fan Shi; Rong Chen; Yong Li (Biochemical Genetics, 2025)

Performance prediction of urban tunnel purification system based on the verified random number screening algorithm - Jie Xia; Hao-Yi Zhao; Hui Ren; Long Chen; Fang Li; Wei-Rong Shi; Yi-Song Xie; Mei-Lan Tan; Fei Li; Bin Zhou (Sustainable Cities and Society, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Cascading impacts of nitrogen deposition on soil microbiome and herbivore communities in desert steppes - Jingxi Liu; Mengmeng Zhu; Xiangfeng Shi; Cang Hui; Yurong Sun; Rong Zhang; Decai Jin; Zhihong Li; Honghao Chen; Zihua Zhao (Science of The Total Environment, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Experimental evaluation of bonded/unbonded prestressed precast concrete joints under repetitive loading scenarios: Seismic performance and retrofit intervention - Hao Fang; Hai-Rong Shi; Xiu-Hang Li; Chun-Lin Wang; Bin Zeng (Engineering Structures, 2024)

Assessment of carbon emissions and reduction potential in China's copper smelting industry - Rong Gao; Yao Shi; Chun Cao; Huiquan Li; Yuanbo Xie; Jingjing Shi; Chenmu Zhang; Xue Guan (Journal of Industrial Ecology, 2024)
As the largest producer and consumer of copper, China is facing enormous challenges from carbon peaking and neutrality. This article adopts “bottom‐up” and “top‐down” methods to construct a more accurate model, to predict the CO 2 emissions of China's copper smelting industry, and explores its potential for carbon reduction in the future from three scenarios as the baseline scenario (BAU), the general low‐carbon (NLC), and the enhanced low‐carbon (ELC). The results show that the CO 2 emissions can achieve a peak in 2028 either in NLC or ELC scenarios, with a peak range of 14.9–16.88 million tonnes. Prior to reaching the peak, the contributions of energy adjustment, material substitution, and process selection to carbon reduction have significantly improved, and the contribution rates increased from 30.91%, 4.11%, and 1.46% to 42.7%, 32.07%, and 15.63% in ELC scenario. After the peak, the contribution of energy adjustment gradually slows down, while the material substitution continues to increase, and the contribution rates increased from 21.25% and 32.07% to 29.38% and 40.01% in NLC and ELC scenarios. In the future, concentrate oxygen‐enriched bottom‐blowing smelting and direct refining from waste copper anode furnaces show ideal potential for carbon reduction before 2025, increasing the proportion of recycled copper production, and adjusting energy structure will be more effective from 2025 to 2035. The conclusions of this study can provide a scientific basis for formulating policy recommendations for green and low‐carbon development of the copper industry in China and all over the world in the future.

Amplification of warming-wetting in high mountains and associated mechanisms during the 21st century in Xinjiang, Central Asia - Rong Chen; Keqin Duan; Peihong Shi; Wei Shang; Junhua Yang; Jinping He; Yali Meng; Mingyu Dou; Liang Li (Climatic Change, 2024)

Study on the Rules of Ground Settlement and Pipeline Deformation Considering the Combined Effects of Pipeline Damage Leakage and Shield Tunneling Construction - Xin Shi; Liang Zheng; Chuanxin Rong; Hua Cheng; Haibing Cai; Taihong Li (Transportation Geotechnics, 2024)

The effect of mixed microbial agents on tobacco black shank disease - Fang Liang; Chai Yunxia; Li Yuanyuan; Geng Shaowu; Bu Yunhong; Hu Yang; Ai Kebiao; Shi Jianfei; Duan Jiyou; Yang Maosong; Zhu Rong (Physiological and Molecular Plant Pathology, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

Enhanced photocatalytic hydrogen evolution via yolk–heteroshell TiO2@TiO2/SiO2 nanoreactor with confined Pt nanoparticles - Haimei Liu; Min Shi; Rong Yang; Ye Wang; Haiyan li; Qiying Su; Tao Wang; Sheng Wang (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Mining of novel target genes through Pan-genome analysis for Conventional PCR and Real-Time PCR detection of Staphylococcus argenteus in food - Jiahui Huang; Jingsha Dai; Ming Liu; Shixuan Huang; Yuwei Wu; Dongli Rong; Yuanyu Li; Miao Zhao; Ying Li; Jumei Zhang; Shi Wu; Qingping Wu (Food Control, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Nervonic acid and its sphingolipids: Biological functions and potential food applications - Nghi Van Phung; Fei Rong; Wan Yue Xia; Yong Fan; Xian Yu Li; Shi An Wang; Fu Li Li (Critical Reviews in Food Science and Nutrition, 2024)

Genetic variation in a heat shock transcription factor modulates cold tolerance in maize - Lei Gao; Lingling Pan; Yiting Shi; Rong Zeng; Minze Li; Zhuoyang Li; Xuan Zhang; Xiaoming Zhao; Xinru Gong; Wei Huang; Xiaohong Yang; Jinsheng Lai; et al. (Molecular Plant, 2024)

Ca2+-nano starch-lutein endowed 3D printed surimi with antioxidation and mutual reinforcing transmembrane transport mechanisms via hepg2 and caco-2 cells model - Gaoshang Li; Rong Shi; Junqi Zhan; Yiduo Wu; Yue Wan; Qian Yao; Yaqin Hu; Chunhua Wu; Wenge Yang; Wubo Wan (Food Research International, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Informer-Based Model for Long-Term Ship Trajectory Prediction - Caiquan Xiong; Hao Shi; Jiaming Li; Xinyun Wu; Rong Gao (Journal of Marine Science and Engineering, 2024)
Ship trajectory prediction is a complex time series forecasting problem that necessitates models capable of accurately capturing both long-term trends and short-term fluctuations in vessel movements. While existing deep learning models excel in short-term predictions, they struggle with long-sequence time series forecasting (LSTF) due to difficulties in capturing long-term dependencies, resulting in significant prediction errors. This paper proposes the Informer-TP method, leveraging Automatic Identification System (AIS) data and based on the Informer model, to enhance the ability to capture long-term dependencies, thereby improving the accuracy of long-term ship trajectory predictions. Firstly, AIS data are preprocessed and divided into trajectory segments. Secondly, the time series is separated from the trajectory data in each segment and input into the model. The Informer model is utilized to improve long-term ship trajectory prediction ability, and the output mechanism is adjusted to enable predictions for each segment. Finally, the proposed model’s effectiveness is validated through comparisons with baseline models, and the influence of various sequence lengths Ltoken on the Informer-TP model is explored. Experimental results show that compared with other models, the proposed model exhibits the lowest Mean Squared Error, Mean Absolute Error, and Haversine distance in long-term forecasting, demonstrating that the model can effectively capture long-term dependencies in the trajectories, thereby improving the accuracy of long-term vessel trajectory predictions. This provides an effective and feasible method for ensuring ship navigation safety and advancing intelligent shipping.

Timing and Kinematics of late Cenozoic Strike-slip Faults in the Western Tibetan Plateau: New Constraints from Provenance Analysis and Detrital Thermochronology - Xiaochun Wei; Hanlin Chen; Rong Yang; Ping Wang; Shanying Li; Xuhua Shi; Jin Ge (Tectonophysics, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

In situ visualization on the mobility of mineral associated organic matter in a microfluidics-based heterogeneous soil aggregate structure - Minru Cheng; Mingang Dong; Peng Liao; Haoran Wang; Zhenqing Shi; Rong Li (Journal of Hydrology, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Catalytic hydrotreatment of fast pyrolysis liquids from Pine wood using Ru-based catalysts supported on nitrogen-doped carbon materials - Yunhui Xia; Nan Xi; Xinyang Yu; Maohua Luo; Shi Chen; Qinglian Wang; Yixiong Lin; Rong Wang; Hao Li; Jun Yue; Chen Yang; Wang Yin; et al. (Fuel, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Radio frequency heating induced 3D printed white croaker (Argyrosomus argentatus) surimi gelation: Effectiveness and gel quality evaluation - Yaxing Yang; Feifan Cao; Rong Han; Feng Li; Hu Shi; Fanbin Kong; Yang Jiao (Innovative Food Science & Emerging Technologies, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Geomorphic expression of transverse drainages across the Tugerming anticline, southern Tian Shan: Implications for the river-fold interaction in the foreland - Feng Li; Xuhua Shi; Julien Charreau; Xiaogan Cheng; Rong Yang; Hanlin Chen; Jin Ge; Jinghan Wang (Journal of Structural Geology, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

A layered sodium-ion host O3-NaFe0.5Ti0.5O2 enables Na-free cathodes through offering extractable Na-ions - Qingyang Song; Peng Shi; Zhiqiang Guo; Peng Zhang; Yuanhang Li; Xiaohui Rong; Xiaoyan Wu; Shuyin Xu; Huican Mao; Yingchun Lyu; Chengjun Zhu (Chemical Engineering Journal, 2024)

Soil Carbon Mineralization and Aggregate Distribution in Various Tillage Practices of Rice–Wheat Cropping System: A Field and Laboratory Study - Naeem Ahmad; Ahmad Latif Virk; Muhammad Bilal Hafeez; Zheng-Rong Kan; Zujiao Shi; Rui Wang; Hafiz Muhammad Waleed Iqbal; Muhammad Ishaq Asif Rehmani; Xiaoli Wang; Rattan Lal; Jun Li (Journal of Soil Science and Plant Nutrition, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Preparation of potential organic fertilizer rich in γ-polyglutamic acid via microbial fermentation using brewer's spent grain as basic substrate - Fengqing Wang; Yanmei Chen; Jia Zheng; Can Yang; Li Li; Rong Li; Meilin Shi; Zhongxuan Li (Bioresource Technology, 2024)

Gut microbiome as a key monitoring indicator for reintroductions of captive animals - Guangping Huang; Dunwu Qi; Zhisong Yang; Rong Hou; Wenyu Shi; Fangqing Zhao; Zitian Li; Li Yan; Fuwen Wei (Conservation Biology, 2024)
Reintroduction programs seek to restore degraded populations and reverse biodiversity loss. To examine the hypothesis that gut symbionts could be used as an indicator of reintroduction success, we performed intensive metagenomic monitoring over 10 years to characterize the ecological succession and adaptive evolution of the gut symbionts of captive giant pandas reintroduced to the wild. We collected 63 fecal samples from 3 reintroduced individuals and 22 from 9 wild individuals and used 96 publicly available samples from another 3 captive individuals. By microbial composition analysis, we identified 3 community clusters of the gut microbiome (here termed enterotypes ) with interenterotype succession that was closely related to the reintroduction process. Each of the 3 enterotypes was identified based on significant variation in the levels of 1 of 3 genera: Clostridium , Pseudomonas , and Escherichia . The enterotype of captive pandas was Escherichia . This enterotype was gradually replaced by the Clostridium enterotype during the wild‐training process, which in turn was replaced by the Pseudomonas enterotype that resembled the enterotype of wild pandas, an indicator of conversion to wildness and a successful reintroduction. We also isolated 1 strain of Pseudomonas protegens from the wild enterotype, a previously reported free‐living microbe, and found that its within‐host evolution contributed to host dietary adaptation in the wild. Monitoring gut microbial structure provides a novel, noninvasive tool that can be used as an indicator of successful reintroduction of a captive individual to the wild.

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Applicability evaluation of innovative simplified methods of slatted floor in pig houses – A CFD study - Fei Qi; Xuedong Zhao; Zhengxiang Shi; Li Rong; Guoqiang Zhang; Hao Li (Computers and Electronics in Agriculture, 2024)

Soil moisture dynamics regulates the release rates and lability of copper in contaminated paddy soils - Yijin Lv; Jialiang Kuang; Zecong Ding; Rong Li; Zhenqing Shi (Science of The Total Environment, 2024)

Influence of drought intensity on soil carbon priming and its temperature sensitivity after rewetting - Rui Zhang; Rong Li; Jialiang Kuang; Zhenqing Shi (Science of The Total Environment, 2024)

Shifted plant composition predominantly controls nitrogen addition effect on community-level leaf nutrient resorption in a boreal peatland - Rui Li; Pan-Pan Wu; Chao Peng; Fu-Xi Shi; Rong Mao (Plant and Soil, 2024)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Prevalence and characterization of Staphylococcus aureus and Staphylococcus argenteus isolated from rice and flour products in Guangdong, China - Dongli Rong; Zhenjie Liu; Jiahui Huang; Feng Zhang; Qingping Wu; Jingsha Dai; Yuanyu Li; Miao Zhao; Qi Li; Jumei Zhang; Shi Wu (International Journal of Food Microbiology, 2023)

Review of silicon recovery in the photovoltaic industry - Yuelong Yu; Xinjie Bai; Shaoyuan Li; Jianghao Shi; Lei Wang; Fengshuo Xi; Wenhui Ma; Rong Deng (Current Opinion in Green and Sustainable Chemistry, 2023)

Analysis of mRNA and MicroRNA Expression Profiles of Nervous Tissues and Reproductive Tissues in Male Procambarus clarkii After Silencing IAG - Rong Sun; Shaokui Yi; Linlin Shi; Kianann Tan; Ruixue Shi; Siqi Yang; Yanhe Li (Marine Biotechnology, 2023)

Projected Regional 1.50°C and 2.00°C Warming Threshold-crossing Time Worldwide Using the CMIP6 Models - Yali Meng; Keqin Duan; Wei Shang; Peihong Shi; Shuangshuang Li; Ying Cheng; Rong Chen; Zhaopeng Zhang (Chinese Geographical Science, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Characteristics of landscape and erosion in the Eastern Pamir and their implications for regional fault connections - Yunpeng Wu; Rong Yang; Junqing He; Hanlin Chen; Xiubin Lin; Xuhua Shi; Kaixuan An; Chunyang Li; Shibao Gao; Yaguang Chen (Geomorphology, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Sensitive temperature changes on the Tibetan Plateau in response to global warming - Yali Meng; Keqin Duan; Peihong Shi; Wei Shang; Shuangshuang Li; Ying Cheng; Li Xing; Rong Chen; Jinping He (Atmospheric Research, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Fatigue life analysis of offshore wind turbine under the combined wind and wave loadings considering full-directional wind inflow - Bing Li; Haiyang Shi; Kang Rong; Weijuan Geng; Yongxin Wu (Ocean Engineering, 2023)

Remediating petroleum hydrocarbons in highly saline–alkali soils using three native plant species - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yanhong Liu; Rong Ma; Ruijie Li; Leiping Shi (Journal of Environmental Management, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

A study of the lipid profile of Coix seeds from four areas based on untargeted lipidomics combined with multivariate algorithms to enable tracing of their origin - Peng Chen; Yabo Shi; Xiaoyan Xiao; Rong Xue; Yu Li; Lin Li; Chunqin Mao; Tulin Lu; Conglong Xu (Food Research International, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

Chemical weathering in the Himalayan system in response to the evolution of the Indian summer monsoon since 37 ka - Long Tan; Jianguo Liu; Yun Huang; Rong Xiang; Shengfa Liu; Hui Zhang; Jingrui Li; Linghui Yu; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Mechanistic insights into effect of in-situ microplastics on heavy metals leaching behavior from its dyeing sludge incineration bottom ash - Xiaoao Shi; Hao Rong; Jinping Li; Yifan Zhao; Lu Ren; Si Chen; Jingxin Liu; Meng Mei; Yongjie Xue; Teng Wang (Journal of Environmental Chemical Engineering, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Nitrogen addition mediates monospecific and mixed litter decomposition in a boreal peatland - Xiong-Fei Zhang; Nan-Hai Zhong; Rui Li; Fu-Xi Shi; Rong Mao (CATENA, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Influence mechanism of organic matter and low-molecular-weight organic acids on the interaction between minerals and PAHs - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yan hong Liu; Rong Ma; Ruijie Li; LeiPing Shi (Science of The Total Environment, 2023)

The emergence of novel macrolide resistance island in Macrococcus caseolyticus and Staphylococcus aureus of food origin - Feng Zhang; Shi Wu; Jingsha Dai; Jiahui Huang; Jumei Zhang; Miao Zhao; Dongli Rong; Yuanyu Li; Juan Wang; Moutong Chen; Liang Xue; Yu Ding; et al. (International Journal of Food Microbiology, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities - Dao-Qun Shi; Jia-Jin Liu; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2023)

A ca. 290 Ma hydrothermal calcite in Cambrian dolostone - Zhongwu Lan; Shitou Wu; Fangyue Wang; Bo Liu; Kaibo Shi; Jing Sun; Rong Cao; Xian-Hua Li (Marine and Petroleum Geology, 2023)

Discovery of a fossil dwarf antelope outside of Africa and its implications for the late Miocene ecosystem in the northeast margin of the Tibetan Plateau - Shi-Qi Wang; Jimin Sun; Chunxiao Li; Shi-Jie Li; Jiao Fu; Qigao Jiangzuo; Luda Xing; Rong Yang (Gondwana Research, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Hominibacterium faecale gen. nov., sp. nov., an anaerobic l-arginine-degrading bacterium isolated from human feces - Noori Borhanudin; Min Yang; Andrei V. Chaplin; Jiang Li; Qiong Wang; Li-rong Dai; Ke-jia Wu; Shi-chun Ma; Boris A. Efimov; Lei Cheng (Archives of Microbiology, 2023)

The Improving of Cd2+ Adsorption Performance of Hydrochar Obtained from Corn Straw Waste with KOH Activation - Yan Shi; Heng Li; Yushi Rong; Li Bai; Mingshu Chi; Xiuling Xu; Chenglin Li; Hao Bai; Yue Liu (Water, Air, & Soil Pollution, 2022)

Preparation of Pinocembrin-Loaded F127/MPEG-PDLLA Polymer Micelles and Anti-Osteoporotic Activity - Xia Cao; Qing He; Michael Adu-Frimpong; Xinyi Shen; Wanjing Rong; Xiaoxiao Li; Jian Zhang; Xiaoli Xia; Feng Shi; Hao Ji; Elmurat Toreniyazov; Qilong Wang; et al. (AAPS PharmSciTech, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

MicroRNA-339-5p inhibits lipopolysaccharide-induced rat mesangial cells by regulating the Syk/Ras/c-Fos pathway - Jia Rong Gao; Miao Miao Shi; Hui Jiang; Xiao Li Zhu; Liang Bing Wei; Xiu Juan Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Sugar Product Diversification and Its Opportunities in China - Qi Wang; Cai-Feng Xie; Chang-Rong Shi; Yuan Li; Yu-Hao Shang; Chu-Xuan Hou; Fang-Xue Hang; Jian-Bin Li; Kai Li (Sugar Tech, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer - Li-rong Yan; Han-xi Ding; Shi-xuan Shen; Xiao-dong Lu; Yuan Yuan; Qian Xu (Functional & Integrative Genomics, 2021)

AsTal1 from Aquilaria sinensis regulates ABA signaling-mediated seed germination and root growth in Nicotiana benthamiana - Yuqing Rong; Tiezheng Li; Xiao Liu; Shepo Shi; Xiaohui Wang; Pengfei Tu (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Dietary Supplementation with Sea Cucumber Saponins and Exercise Can Significantly Suppress Adipose Accumulation in Mice Fed with High-Fat Diet - Rong Li; Jing Meng; Haohao Shi; Chengcheng Wang; Zhaojie Li; Changhu Xue; Yuming Wang; Tiantian Zhang (Journal of Ocean University of China, 2021)

Environmental Governance of Western Europe and Its Enlightenment to China: In Context to Rhine Basin and the Yangtze River Basin - Wangjinyu Shi; Yangyang Wu; Xue Sun; Xueyuan Gu; Rong Ji; Mei Li (Bulletin of Environmental Contamination and Toxicology, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Influence of leaf shape on the scaling of leaf surface area and length in bamboo plants - Pei-Jian Shi; Yi-Rong Li; Ülo Niinemets; Edward Olson; Julian Schrader (Trees, 2021)
Key message Using more than 10,000 bamboo leaves, we found that the scaling between leaf surface area and length follows a uniform power law relationship mainly relying on the degree of variation in leaf shape (reflected by the ratio of leaf width to length). Abstract A recent study based on leaf data of different plant taxa showed that the scaling of leaf surface area ( A ) with linear leaf dimensions was best described by the Montgomery equation (ME) that describes A as the product of leaf length ( L ) and width ( W ). Following from ME, a proportional relationship between A and the square of L has been proposed, but the validity of this simplified equation strongly depends on leaf shape ( W/L ratio). Here, we show that the simplified equation can be applied to a group of closely related plants sharing a similar W/L ratio with low degree of uncertainty. We measured A , L and W of more than 10,000 leaves from 101 graminoid taxa (subfamily Bambusoideae) having similar elongated leaf shapes. We found that ME applies to the leaves of all bamboo taxa investigated. The power law equation that was used to describe a scaling relationship of A vs. L also predicted leaf area with high accuracy, but the variability measured as the root-mean-square error (RMSE) was greater than that using ME, indicating that leaf width also plays an important role in predicting leaf area. However, the dependence of the prediction accuracy of A on W is intimately associated with the extent of the variation in W/L ratio. There was a strong positive correlation ( r = 0.95 for the 101 bamboo taxa) between RMSE and the coefficient of variation in W/L ratio. Thereby, our results show that leaf area of bamboo plants can be calculated by the product of L and W with a proportionality coefficient ranging from 0.625 to 0.762, i.e., the leaf area of bamboo leaves approximately equals 70% of a rectangular area formed by L and W . The pooled data of ln( A ) vs. ln( WL ) of 101 bamboo taxa were located on or very close to the regression line without being affected by interspecific differences. However, interspecific differences in W/L ratio largely affected the scaling relationship of A vs. L , which led to large deviations of the data of ln( A ) vs. ln( L ) from the regression line. This implies that the square relationship between A and L does not apply to all species even if those are very closely related taxa.

Sediment Structures Constrained by Converted Waves From Local Earthquakes Recorded by a Dense Seismic Array in the Tangshan Earthquake Region - Feng Bao; Zhiwei Li; Yutao Shi; Baofeng Tian; Jiajun Chong; Weijian Rong (Pure and Applied Geophysics, 2021)

Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine - Mei-Rong Zhang; Kan Jiang; Jun-Li Yang; Yan-Ping Shi (Natural Product Research, 2020)

Mapping quantitative trait loci associated with stem-related traits in maize (Zea mays L.) - Qiqi Shang; Degui Zhang; Rong Li; Kaixin Wang; Zimeng Cheng; Zhiqiang Zhou; Zhuanfang Hao; Jinbao Pan; Xinhai Li; Liyu Shi (Plant Molecular Biology, 2020)

Application of a Two-Analyte Integrated Population Pharmacokinetic Model to Evaluate the Impact of Intrinsic and Extrinsic Factors on the Pharmacokinetics of Polatuzumab Vedotin in Patients with Non-Hodgkin Lymphoma - Dan Lu; Tong Lu; Rong Shi; Leonid Gibiansky; Priya Agarwal; Colby S. Shemesh; Randall C. Dere; Uzor Ogbu; Jamie Hirata; Pascal Chanu; Sandhya Girish; Jin Yan Jin; et al. (Pharmaceutical Research, 2020)
Purpose The established two-analyte integrated population pharmacokinetic model was applied to assess the impact of intrinsic/extrinsic factors on the pharmacokinetics (PK) of polatuzumab vedotin (pola) in patients with non-Hodgkin lymphoma (NHL) following bodyweight-based dosing. Methods Model simulations based on individual empirical Bayes estimates were used to evaluate the impact of intrinsic/extrinsic factors as patient subgroups on Cycle 6 exposures. Intrinsic factors included bodyweight, age, sex, hepatic and renal functions. Extrinsic factors included rituximab/obinutuzumab or bendamustine combination with pola and manufacturing process. The predicted impact on exposures along with the established exposure-response relationships were used to assess clinical relevance. Results No clinically meaningful differences in Cycle 6 pola exposures were found for the following subgroups: bodyweight 100–146 kg versus 38–<100 kg, age ≥ 65 years versus <65 years, female versus male, mild hepatic impairment versus normal, mild-to-moderate renal impairment versus normal. Co-administration of rituximab/obinutuzumab or bendamustine, and change in the pola manufacturing process, also had no meaningful impact on PK. Conclusions In patients with NHL, bodyweight-based dosing is adequate, and no further dose adjustment is recommended for the heavier subgroup (100–146 kg). In addition, no dose adjustments are recommended for other subgroups based on intrinsic/extrinsic factors evaluated.

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Addition of oyster shell to enhance organic matter degradation and nitrogen conservation during anaerobic digestate composting - Ming-Yi Lu; Xiao-Shuang Shi; Xu Li; Shu-Juan Lian; Dong-Yan Xu; Rong-Bo Guo (Environmental Science and Pollution Research, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

Effective identification of CRISPR/Cas9-induced and naturally occurred mutations in rice using a multiplex ligation-dependent probe amplification-based method - Sukumar Biswas; Rong Li; Jun Hong; Xiangxiang Zhao; Zheng Yuan; Dabing Zhang; Jianxin Shi (Theoretical and Applied Genetics, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Root diversity in sesame (Sesamum indicum L.): insights into the morphological, anatomical and gene expression profiles - Ruqi Su; Rong Zhou; Marie Ali Mmadi; Donghua Li; Lu Qin; Aili Liu; Jianqiang Wang; Yuan Gao; Mengyuan Wei; Lisong Shi; Ziming Wu; Jun You; et al. (Planta, 2019)

Symbiotic fungi undergo a taxonomic and functional bottleneck during orchid seeds germination: a case study on Dendrobium moniliforme - Yuan-Yuan Meng; Xu-Li Fan; Lv-Rong Zhou; Shi-Cheng Shao; Qiang Liu; Marc-André Selosse; Jiang-Yun Gao (Symbiosis, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Effects of dietary Sargassum horneri on growth performance, serum biochemical parameters, hepatic antioxidant status, and immune responses of juvenile black sea bream Acanthopagrus schlegelii - Qingchao Shi; Hua Rong; Meilin Hao; Dashi Zhu; Jude Juventus Aweya; Shengkang Li; Xiaobo Wen (Journal of Applied Phycology, 2019)

Development of methods for effective identification of CRISPR/Cas9-induced indels in rice - Sukumar Biswas; Rong Li; Zheng Yuan; Dabing Zhang; Xiangxiang Zhao; Jianxin Shi (Plant Cell Reports, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

EZH2 promotes cell proliferation by regulating the expression of RUNX3 in laryngeal carcinoma - Rong Lian; Huimin Ma; Zhiyan Wu; Guozheng Zhang; Lei Jiao; Wenjie Miao; Qianqian Jin; Ruixue Li; Ping Chen; Haixu Shi; Wenfa Yu (Molecular and Cellular Biochemistry, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

Green Synthesis of Sucrose Laurate Under Different Ultrasonic Frequencies - Fang-xue Hang; Chang-rong Shi; Yong-shi Xu; Hai-qin Lu; Cai-feng Xie; Kai Li (Sugar Tech, 2017)

Erratum to: Acidic domains differentially read histone H3 lysine 4 methylation status and are widely present in chromatin-associated proteins - Meng Wu; Wei Wei; Jiwei Chen; Rong Cong; Tieliu Shi; Philippe Bouvet; Jiwen Li; Jiemin Wong; James X. Du (Science China Life Sciences, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

Protein tyrosine phosphatase 1B expression contributes to the development of breast cancer - Shi-chong Liao; Jin-xin Li; Li Yu; Sheng-rong Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Acidic domains differentially read histone H3 lysine 4 methylation status and are widely present in chromatin-associated proteins - Meng Wu; Wei Wei; Jiwei Chen; Rong Cong; Tieliu Shi; Jiwen Li; Jiemin Wong; James X. Du (Science China Life Sciences, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

P2Y6 Receptor-Mediated Microglial Phagocytosis in Radiation-Induced Brain Injury - Yongteng Xu; Weihan Hu; Yimin Liu; Pengfei Xu; Zichen Li; Rong Wu; Xiaolei Shi; Yamei Tang (Molecular Neurobiology, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

One-step reverse transcription loop-mediated isothermal amplification assay for rapid detection of melon yellow spot virus - Rong Zeng; Li-hui Xu; Shi-gang Gao; Xiu-hong Ni; Chun-lei Chen; Jian-cai Chen; Fu-ming Dai (European Journal of Plant Pathology, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Induction of follicular luteinization by equine chorionic gonadotropin in cyclic guinea pigs - Jun-rong Li; Wei Wang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2015)

The effects of grafting on glycolysis and the tricarboxylic acid cycle in Ca(NO3)2-stressed cucumber seedlings with pumpkin as rootstock - Lin Li; Wen-wen Xing; Qiao-sai Shao; Sheng Shu; Jin Sun; Shi-rong Guo (Acta Physiologiae Plantarum, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Determination of tumorigenic Agrobacterium density in soil by real-time PCR assay and its effect on crown gall disease severity - Qian Li; Rong-Jun Guo; Shi-Dong Li; Shi-Fang Li; Hong-Qing Wang (European Journal of Plant Pathology, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Fungus Exposed Solenopsis invicta Ants Benefit from Grooming - Hua-long Qiu; Li-hua Lu; Qing-xing Shi; Yu-rong He (Journal of Insect Behavior, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Effects of High Zinc Levels on the Lipid Synthesis in Rat Hepatocytes - Xinwei Li; Yuan Guan; Xiaoxia Shi; Hongyan Ding; Yuxiang Song; Chenggang Li; Rong Liu; Guowen Liu (Biological Trace Element Research, 2013)

Potential hepatotoxicity of geniposide, the major iridoid glycoside in dried ripe fruits of Gardenia jasminoides (Zhi-zi) - Yue Ding; Tong Zhang; Jian-sheng Tao; Li-ying Zhang; Jian-rong Shi; Guang Ji (Natural Product Research, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Mapping of quantitative trait loci for oil content in cottonseed kernel - QUAMPAH ALFRED†; HAI YING LIU†; HAI MING XU; JIN RONG LI; JIAN GUO WU; SHUI JIN ZHU; CHUN HAI SHI (Journal of Genetics, 2012)

Polymorphisms of the interleukin-15 gene and their associations with fatness and muscle fiber traits in chickens - Shi-Jie Lv; Ling Su; Hong Li; Rui-Li Han; Gui-Rong Sun; Xiang-Tao Kang (Journal of Applied Genetics, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

Perifosine as potential anti-cancer agent inhibits proliferation, migration, and tube formation of human umbilical vein endothelial cells - Feng Ze Wang; Hong Rong Fei; Xiao Qian Li; Renjiu Shi; De Cai Wang (Molecular and Cellular Biochemistry, 2012)

Association between SHBG Asp327Asn (rs6259) polymorphism and breast cancer risk: a meta-analysis of 10,454 cases and 13,111 controls - Jue-Yu Zhou; Rong Shi; Hai-Lang Yu; Wen-Ling Zheng; Wen-Li Ma (Molecular Biology Reports, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Protective effect of andrographolide against concanavalin A-induced liver injury - Guojun Shi; Zhijian Zhang; Rong Zhang; Xiaofang Zhang; Yan Lu; Jian Yang; Di Zhang; Zhiguo Zhang; Xiaoying Li; Guang Ning (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Ocular Pharmacokinetic Study Using T1 Mapping and Gd-Chelate- Labeled Polymers - Xianfeng Shi; Xin Liu; Xueming Wu; Zheng-Rong Lu; S. Kevin Li; Eun-Kee Jeong (Pharmaceutical Research, 2011)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Changes in soil biochemical properties associated with Ligularia virgaurea spreading in grazed alpine meadows - Xiao Ming Shi; Xiao Gang Li; Rong Mei Wu; Yun Hui Yang; Rui Jun Long (Plant and Soil, 2011)

Overexpression of a cytosolic glyceraldehyde-3-phosphate dehydrogenase gene OsGAPC3 confers salt tolerance in rice - Xiu-Hong Zhang; Xiao-Lan Rao; Hai-Tao Shi; Rong-Jun Li; Ying-Tang Lu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Halomonas qijiaojingensis sp. nov. and Halomonas flava sp. nov., two moderately halophilic bacteria isolated from a salt lake - Chao Chen; Rong Shi; Bing-Bing Liu; Yun-Jiao Zhang; Hong-Zhuan Sun; Chang-Tian Li; Shu-Kun Tang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Chlorothalonil degradation by Ochrobactrum lupini strain TP-D1 and identification of its metabolites - Xiu-Zhen Shi; Rong-Jun Guo; Kazuhiro Takagi; Zuo-Qing Miao; Shi-Dong Li (World Journal of Microbiology and Biotechnology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Molecular phylogenetic reconstruction of Osmanthus Lour. (Oleaceae) and related genera based on three chloroplast intergenic spacers - Shi-Quan Guo; Min Xiong; Chun-Feng Ji; Zhi-Rong Zhang; De-Zhu Li; Zhi-Yong Zhang (Plant Systematics and Evolution, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Effects of elevated CO2 levels on root morphological traits and Cd uptakes of two Lolium species under Cd stress - Yan Jia; Shi-rong Tang; Xue-hai Ju; Li-na Shu; Shu-xing Tu; Ren-wei Feng; Lorenzino Giusti (Journal of Zhejiang University-SCIENCE B, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

A new hexenol glycoside from leaves of Smallanthus sonchifolius - Xiang Zheng; Gai Kuo; Dou De-Qiang; Chen Gui-Rong; Kang Ting-Guo; Shi Yu-Yuan; Li Xing-Tai; Dong Feng (Natural Product Research, 2010)

Genetic Diversity and Geographical Differentiation of Desmodium triflorum (L.) DC. in South China Revealed by AFLP Markers - Mao-feng Yue; Ren-chao Zhou; Ye-lin Huang; Guo-rong Xin; Su-hua Shi; Li Feng (Journal of Plant Biology, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Effects of exogenous putrescine on gas-exchange characteristics and chlorophyll fluorescence of NaCl-stressed cucumber seedlings - Run Hua Zhang; Jun Li; Shi Rong Guo; Takafumi Tezuka (Photosynthesis Research, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

A preliminary study on the teratogenesis of dexamethasone and the preventive effect of vitamin B12 on murine embryonic palatal shelf fusion in vitro - Sheng-jun Lu; Wei He; Bing Shi; Tian Meng; Xiao-yu Li; Yu-rong Liu (Journal of Zhejiang University-SCIENCE B, 2008)

Characterizing and estimating rice brown spot disease severity using stepwise regression, principal component regression and partial least-square regression - Zhan-yu Liu; Jing-feng Huang; Jing-jing Shi; Rong-xiang Tao; Wan Zhou; Li-li Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Mutation induced by ethylmethanesulphonate (EMS), in vitro screening for salt tolerance and plant regeneration of sweet potato (Ipomoea batatas L.) - Yu-Shi Luan; Juan Zhang; Xiao-Rong Gao; Li-Jia An (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Residents’ attitudes to tourism development in ancient village resorts - Li Wang; Lin Lu; Shi-rong Tong; Song Lu; Zhao Yang; Yong Wang; Dong-dong Liang (Chinese Geographical Science, 2004)

Genetic analysis and breeding use of blast resistance in a japonica rice mutant R917 - Ming Xian Zhang; Jian Long Xu; Rong Ting Luo; De Shi; Zhi Kang Li (Euphytica, 2003)